A study on the factors influencing employees' comptetency through organizational learning: A case of Malaysian islamic insurance company / Siti Nadzirah Samingin - Samingin, Siti Nadzirah (Faculty of Business Management, 2015)
This paper investigates aimed at broadening the understanding of organizational learning can influence towards employees’ competency in managing a Malaysian Islamic Insurance Company. Focusing on the three main offices at Southern branch of Prudential BSN Takaful Berhad, a total of 150 respondents from a staff were selected to participate in this study. With the assumption that organizational learning is all about organizational actions through better learning concepts, interesting activities prepared and full knowledge or as the outcome of such processes in order to make their employees more competitive, efficient and high competency in their tasks. Based on the earlier studies, the researcher suggested that there are eleven (11) dimensions (features) were necessarily in measuring to what extent the organization is actively pursuing the concept of organizational learning. However, this paper only discovered and focuses to only five (5) features of organizational learning that are able to demonstrate its usefulness towards influencing employees’ competency at the selected company. In this research, Internal exchange, reward flexibility, learning climate, informating and learning approaches and participative policy making are five variables that are used as the pre-determined factors in measuring employees’ competency through organizational learning. It is expected that the findings of this study will assist the organization to be more concerned about the activity to enhance the competency of its employees, improve organizational effectiveness, thus maintaining the competitive advantage in the industry.